Isolation, identification and molecular characterization of feline coronavirus in Malaysia - Al-Azawy, Amer Khazaal Salih (2011)
Feline infectious peritonitis virus (FIPV) and feline enteric coronavirus (FECV) are coronaviruses causing disease in cats. FIPV is a highly fatal and immune-mediated pyogranulomatous disease, whereas FECV is asymptomatic and a subclinical or mild enteric infection. Both FIPV and FECV are further subdivided into serotypes I and II. Cases of FIP occur in young and adult cats with varying degree of severity. In Malaysia, Feline coronavirus (FCoV) is prevalent where 100% of cats in catteries developed antibodies against the feline coronavirus. However, 84% of cats kept in catteries and shelters, were found to have viral genome of feline coronavirus in their feces. FIP is believed to be mutated from FECV and the virus has tropism towards the macrophages. Although many cats can be infected with FCoV, only 10% will develop FIP disease. There is no effective vaccine to control the disease because immunized cats are found to be more susceptible to infection than unvaccinated cats due to the antibody-dependent enhancement (ADE) phenomena. Although the FCoV is prevalent in Malaysia, the virus causing the disease has not been characterized and serotype. The study was conducted to isolate, identify, characterize and type the local feline coronavirus. The local isolates and two reference strains of FCoV were compared with respect to their biological properties, morphology and genome homology. A total of 42 cats clinically suspected of having FIP disease were obtained during the 4 years period (2007-2010) and were designated as UPM1C/07 to UPM42C/10. Affected cats showing respiratory distress with distended abdominal cavity were sampled. Ascites fluid or tissues from cat dying from FIP were screened for FCoV by a one-step reverse transcriptase polymerase chain reaction (RT-PCR) assay and adapted in Crandell feline kidney (Crfk) and Felis catus whole foetus (Fcwf-4) cell cultures. About 95% (40/42) of them were positive by virus isolation and confirmed by RT-PCR. Upon infection into two cell lines, infected cells showed cytopathic effect (CPE) characterised by giant cells, ballooning and detachment of infected cells. Fcwf-4 cell line provides more suitable growth conditions for local isolate FCoVs. Representative of three FCoV isolates namely the UPM5C/O8, UPM11C/08 and UPM24C/09 were clone purified by limiting dilution and were used for subsequent studies. Identification of the virus isolates was conducted by indirect immunofluorescent (IIF), indirect immunoperoxidase (IIP), haematoxylin and eosin staining (H&E) and transmission electron microscope (TEM). The study showed that FCoV multiply in the cytoplasm of infected cells. The virus particles possessed the characteristic of coronavirus with spherical shapes and surrounded by club shaped peplomers indicative of typical coronavirus. The determination of the serotypes of local FCoV and their phylogenetic relatedness was performed by analyzing their S gene region using published primers. Following analyses, 97.5% and 2.5% of local FCoV isolates belonged to serotypes I and II, respectively. Phylogenetic analysis performed on selected 12 FCoV type I local isolates on the S region showed that the homology amongst them ranged from 92.3-100% and decreased to 90% with reference viruses. Whereas the local FCoV type II has 97.5-99% homology with reference strains. Malaysian FCoV isolates fall in 3 clusters where 2 clusters comprise most of type I which are closer to the USA, Netherlands, UK, Japan and Taiwan isolates, and third cluster comprises the type II which is in the group of reference viruses of USA and Italy. In conclusion, this is the first detailed study on isolated local feline coronavirus in an attempt to adapt the viruses in vitro and characterize them. About 95% (40/42) of cats that were naturally infected with feline coronavirus have the viral genome in their body excretion. The isolated viruses were adaptable in cell culture and induce of cytopathic effect. FCoV type I was highly prevalent amongst the local cats.